Buerger-Allen exercises' effectiveness for improving lower limb circulation - Hesti Prawita Widiastuti; Rahmawati Paonganan; Diah Setiani; Arsyawina Arsyawina; Joko Sapto Pramono; Hilda Hilda (PAGEPress Publications, 2024)
Impaired peripheral perfusion in the legs is the most common complaint experienced by patients with type 2 Diabetes Mellitus (DM). One nursing intervention in the form of physical exercise that can be administered to DM patients to prevent peripheral perfusion disorders and increase vascularization of the lower extremities is the Buerger-Allen Exercise (BAE). The goal of this study was to analyze the effectiveness of BAE in improving lower extremity circulation. The population consisted of patients with type 2 DM. The research design employed a quasi-experiment with pre-test and post-test, including a control group. A sample of 24 respondents was divided into an intervention group and a control group. The sampling technique used was purposive sampling. Data were obtained through direct Ankle-Brachial Index (ABI) measurement using a Doppler ultrasound and an aneroid sphygmomanometer, temporary blood sugar level measurements using a glucometer, and leg sensitivity measurements using a monofilament tool. Paired T-tests and independent T-tests were used as statistical tests. The results of the Paired T-test for lower limb circulation in the intervention group yielded a p-value of 0.000, indicating a significant difference in the circulation of the lower extremities before and after the intervention. The results of the independent T-test also showed a p-value of 0.000, indicating significance. Thus, BAE can improve lower limb circulation in patients with type 2 DM.